2009
DOI: 10.1038/bmt.2009.159
|View full text |Cite
|
Sign up to set email alerts
|

Mannose-binding lectin levels and infections in children after allogeneic hematopoietic SCT

Abstract: Mannose-binding lectin (MBL) is an activator of the lectin pathway of the C 0 system and hence an important component of the innate immune system. Although reports are conflicting, MBL deficiency has been reported to influence the infection susceptibility in hematology/ oncology patients or recipients of allogeneic hematopoietic SCT (HSCT). MBL levels and the occurrence of infections were retrospectively analyzed in 98 pediatric HSCT patients. MBL deficiency in recipients was not corrected by HSCT using a dono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 19 publications
(29 reference statements)
0
11
2
Order By: Relevance
“…26 Previous studies on the role of complement MBL in patients after allogeneic stem cell transplantation demonstrated conflicting results irrespective of the chosen definition of functional MBL deficiency. 14,[21][22][23][24][25] Recently, Neth et al for the first time found an association of low MBL levels and severe infections in patients after allogeneic stem cell transplantation. 25 In contrast to this study and our results the occurrence of major infections was not related to low MBL levels in the studies presented by Mullighan et al and Chaudhry et al 14,24 However, besides differences in patients' characteristics (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…26 Previous studies on the role of complement MBL in patients after allogeneic stem cell transplantation demonstrated conflicting results irrespective of the chosen definition of functional MBL deficiency. 14,[21][22][23][24][25] Recently, Neth et al for the first time found an association of low MBL levels and severe infections in patients after allogeneic stem cell transplantation. 25 In contrast to this study and our results the occurrence of major infections was not related to low MBL levels in the studies presented by Mullighan et al and Chaudhry et al 14,24 However, besides differences in patients' characteristics (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…12 Even during acute inflammation, MBL serum concentrations are predictive for moderate to severe deficiency. 8,13,14 Evidence from several studies of the last 20 years supports a strong association between MBL deficiency and the risk of infections, particularly when adaptive immunity is either immature or compromised (e.g. during early childhood [15][16][17] or after solid organ transplantation [18][19][20] ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations are in line with those obtained in a similar previous study of pediatric HSCT patients, in which MBL levels of o400 ng/mL were also not associated with an increased infection rate. 6 The findings in studies investigating adult-HSCT recipients, on the other hand, are inconsistent. In those, low MBL levels had either no effect on the risk of infection 3 or, they had even a negative impact on the infection risk under particular circumstances, for instance in case of TBI.…”
Section: Resultsmentioning
confidence: 89%
“…In consideration of the so far inconsistent findings of the role of MBL in HSCT in adult, [2][3][4][5] as well as pediatric 6 HSCT, we prospectively investigated the impact of MBL levels, genotypes and MASP-2 levels in a series of 99 pediatric (n = 96) and young adult (n = 3) HSCT recipients. MBL deficiency was defined by MBL levels o 300 ng/mL and/or particular MBL haplotypes.…”
mentioning
confidence: 99%